Artificial Intelligence–Driven Advancements in Dental Implants: A Narrative Review - Sowmiya, Srinivasan; Sridharan, Rajendran; Indirajith, Shiyam Sundhar; Jeyakumar, lda Esther Celina; Leoney, Antony (International Journal of Dental Materials, 2025)
We are in the era of advancements with digital innovative technologies, which have taken dental systems to the next level through the discovery of artificial intelligence (AI). Recently, AI systems have gained significant popularity in the field of prosthodontics, particularly in implant dentistry. Various studies have emphasized the impact of AI on oral implants, particularly in terms of diagnostic efficiency, treatment planning ability, and subsequent patient outcomes, thereby highlighting the accuracy, rapidity, and precision of decision-making. AI continues to expand in future and promises to amend the view of implant dentistry and lead it to an efficient and personalized part of the oral healthcare system. This review mainly focuses on the advancements of AI-based research in dental implantology and also explores the various applications of AI models. Inclusive data from databases in PubMed, Scopus, Web of Science, and Google Scholar were thoroughly explored, and the role of AI in implant identification, planning, prediction, and complication management was described. Although there are a few drawbacks present, which make AI a challenging factor for continued use in clinical practice. Further research with numerous clinical trials can break through the limitations and be used as an excellent supportive tool.